2021
DOI: 10.3389/fcell.2021.629182
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor Effect of Oleic Acid in Hepatocellular Carcinoma Cell Lines via Autophagy Reduction

Abstract: Oleic acid (OA) is a component of the olive oil. Beneficial health effects of olive oil are well-known, such as protection against liver steatosis and against some cancer types. In the present study, we focused on OA effects in hepatocellular carcinoma (HCC), investigating responses to OA treatment (50–300 μM) in HCC cell lines (Hep3B and Huh7.5) and in a healthy liver-derived human cell line (THLE-2). Upon OA administration higher lipid accumulation, perilipin-2 increase, and autophagy reduction were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 55 publications
2
27
1
1
Order By: Relevance
“…Recent studies have shown that the most common monounsaturated fatty acid in the alimentary diet is oleic, which has protective effects against human diseases, in particular cardiovascular and inflammatory diseases, obesity, and some cancers [48][49][50]. The amounts of DPSO fatty acids reported in previous studies [14,27,31,[51][52][53] were, in general, very similar to the results obtained here.…”
Section: Fatty Acids Compositionsupporting
confidence: 87%
“…Recent studies have shown that the most common monounsaturated fatty acid in the alimentary diet is oleic, which has protective effects against human diseases, in particular cardiovascular and inflammatory diseases, obesity, and some cancers [48][49][50]. The amounts of DPSO fatty acids reported in previous studies [14,27,31,[51][52][53] were, in general, very similar to the results obtained here.…”
Section: Fatty Acids Compositionsupporting
confidence: 87%
“…The decrease in arachidonic acid content was responsible for autophagy activation in breast cancer cells by adipocytes. Specific fatty acids, depending on their unsaturation, were already linked with autophagy regulation, but results remain controversial for the same fatty acids in different models [22][23][24]. Interestingly, it has been demonstrated that unsaturated fatty acids induce a non-canonical form of autophagy, independent of Beclin1 but requiring the Golgi complex [33].…”
Section: Discussionmentioning
confidence: 99%
“…In general, lipids, mostly phospholipids, are associated with the regulation of autophagy since they are direct constituents of the autophagosome membrane, and they participate in the autophagosome formation and fusion with lysosomes, mainly through the regulation of the ubiquitin-like protein conjugation system leading to LC3 conjugation to phosphatidylethanolamine [15]. In addition, specific fatty acids, depending on their unsaturation, can regulate autophagy [22][23][24]. It has been demonstrated that free fatty acids derived from adipocytes induce AMPK activation in breast cancer cells [11], which is a major regulator of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…With great interest we read a paper "Anti-tumor Effect of Oleic Acid in Hepatocellular Carcinoma Cell Lines via Autophagy Reduction" published in Frontiers in Cell and Developmental Biology (Giulitti et al, 2021). Blocking autophagy suppresses the growth of HCC cells (Zai et al, 2020).…”
mentioning
confidence: 99%